Answer:
g(x) =
![9((1)/(3))^x](https://img.qammunity.org/2021/formulas/mathematics/high-school/ga4dkcx5hgiag01iysw8nmgfoq2ntyrrbs.png)
Explanation:
Exponential function 'g' that can be written as g(x) = a.bˣ
From the graph attached,
Graph of the function passes through two points (0, 9) and (1, 3)
g(0) = a.b⁰
9 = a
Similarly, g(1) = a.b¹
3 = a.b
3 = 9(b)
b =
![(3)/(9)=(1)/(3)](https://img.qammunity.org/2021/formulas/mathematics/high-school/hl3tjd5ujmy10ujwbypadaz6pi804xlauw.png)
Therefore function will be,
g(x) =
![9((1)/(3))^x](https://img.qammunity.org/2021/formulas/mathematics/high-school/ga4dkcx5hgiag01iysw8nmgfoq2ntyrrbs.png)